The Significance of חוה in the Book of Joshua: A Theological Examination - Tsegaw, Melak (Jurnal Koinonia: Fakultas Filsafat Universitas Advent Indonesia, 2023)
This paper undertakes a comprehensive exploration of the term "חוה" in the Book of Joshua, delving into two pivotal passages: Joshua 5:13-15 and Joshua 23. The study employs exegetical approaches, incorporating historical, literary, lexical, and syntactical analyses, to elucidate the theological implications inherent in the utilization of this term. In Joshua 5:13-15, the encounter between Joshua and the commander of the army of the Lord serves as a climactic moment in the narrative, symbolizing the apex of Israel's worship during their entry into the Promised Land. The theological implications drawn from Joshua's worship experience serve as foundational principles that guide and inform the nature and essence of Biblical worship, highlighting its responsive, transformative, and reverential dimensions. On the other hand, the theological implications drawn from Joshua's farewell address highlight Biblical worship as a responsive act grounded in God's faithfulness, connected to the covenantal relationship, and exclusively directed towards God. The avoidance of evil associations, close relationship with God, and the ongoing cultivation of love emerge as essential components of meaningful Biblical worship.